2019
DOI: 10.1038/s12276-019-0338-8
|View full text |Cite
|
Sign up to set email alerts
|

VGLL4 interacts with STAT3 to function as a tumor suppressor in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is an aggressive malignancy with a poor prognosis, and there are no effective molecular-targeted drugs for TNBC patients in clinical practice. The JAK-STAT pathway is implicated in tumorigenesis and the progression of various cancers. In this study, the results demonstrated that VGLL4 is expressed at low levels in both TNBC specimens and cell lines and that VGLL4 expression is negatively correlated with Ki67 expression and tumor size in TNBC patients. VGLL4 knockdown can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
3
13
1
Order By: Relevance
“…Interestingly, the increase in STAT3 expression was also seen in the immune‐complex precipitated by pan‐acetylated lysine, ac‐H3K9 and ac‐H3K27 antibodies, and was suppressed after resveratrol treatment, and STAT3 knock down alleviated CNH‐induced PH, indicating that abrogation of VGLL4 acetylation reversed CNH‐induced PH by attenuating STAT3 signaling. However, our results are contrary to those of a recent study conducted by Song et al 50 In that study, the authors reported that inhibiting VGLL4 elevated p‐STAT3 expression and conversely, VGLL4 over‐expression inhibited p‐STAT3 expression. These conflicting results may be due to the differences in the context of the models investigated (PH mice vs. breast cancer).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the increase in STAT3 expression was also seen in the immune‐complex precipitated by pan‐acetylated lysine, ac‐H3K9 and ac‐H3K27 antibodies, and was suppressed after resveratrol treatment, and STAT3 knock down alleviated CNH‐induced PH, indicating that abrogation of VGLL4 acetylation reversed CNH‐induced PH by attenuating STAT3 signaling. However, our results are contrary to those of a recent study conducted by Song et al 50 In that study, the authors reported that inhibiting VGLL4 elevated p‐STAT3 expression and conversely, VGLL4 over‐expression inhibited p‐STAT3 expression. These conflicting results may be due to the differences in the context of the models investigated (PH mice vs. breast cancer).…”
Section: Discussioncontrasting
confidence: 99%
“…Given that maternal vgll4a seemed to act upstream of yap1, we hypothesized that its activity could regulate blastomere adhesion and thus their tension probing capacity. Indeed, in cancer cells VGLL4 regulates the transcription of E-cadherin (Li et al , 2015; Song et al , 2019) and the E-cadherin/α-Catenin/β-Catenin adhesion complex is an upstream regulator of Yap1 in different biological contexts (Kim et al , 2011; Schlegelmilch et al , 2011; Silvis et al , 2011). Furthermore, the epibolic phenotype of MZvgll4a embryos resembled that of the pou5fl/Oct4 deficient MZspg embryos (Lachnit et al , 2008; Song et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…CD44 + /CD24 − stem cell-like population in TNBC tended to be a more aggressive phenotype [ 277 281 ], and cancer stem cell (CSC) was resistant to anoikis by allowing replication independent of anchoring [ 282 , 283 ]. STAT3 could regulate stem cell self-renewal and differentiation and resist anoikis [ 284 , 285 ]. It was also overexpressed and structurally activated in TNBC cells.…”
Section: Targeting Other Rcd Subroutines With Small-molecule Compound...mentioning
confidence: 99%